Sistem Pembelajaran Online Sebagai Mediator Kreativitas SDM, Ketidakpastian Lingkungan, dan Teknologi Informasi pada Kinerja PTS - Pituringsih, Endar; Sokarina, Ayudia; Asmony, Thatok (E-Jurnal Akuntansi, 2022)
The purpose of the study was to examine and find empirical evidence regarding the effect of human resource creativity, environmental uncertainty, and the use of information technology on online learning systems, and the effect of online learning systems on the performance of private universities. The research was conducted at private universities throughout Lombok Island, West Nusa Tenggara Province. The total population in this study is 26 private universities, where each university will make 2 people as samples. So that the sample in this study amounted to 52 respondents. The data analysis method used is the PLS-SEM method. The results of the study stated that the creativity of human resources and the use of information technology had a positive effect on the online learning system. Meanwhile, environmental uncertainty has no effect on the online learning system. Furthermore, the online learning system has a positive effect on the performance of private universities. Keywords: Private Higher Education Performance, Online Learning System, Human Resource Creativity, Environmental Uncertainty, Information Technology